2010
DOI: 10.1128/aac.00812-09
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Cerebrospinal Fluid Inflammation by the Nonbacteriolytic Antibiotic Daptomycin versus That by Ceftriaxone in Experimental Pneumococcal Meningitis

Abstract: Antibiotic-induced bacteriolysis exacerbates inflammation and brain damage in bacterial meningitis. Here the quality and temporal kinetics of cerebrospinal fluid (CSF) inflammation were assessed in an infant rat pneumococcal meningitis model for the nonbacteriolytic antibiotic daptomycin versus ceftriaxone. Daptomycin led to lower CSF concentrations of interleukin 1␤ (IL-1␤), IL-10, IL-18, monocyte chemoattractant protein 1 (MCP-1), and macrophage inflammatory protein 1 alpha (MIP-1␣) (P < 0.05). In experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 20 publications
7
33
0
Order By: Relevance
“…For rifampin, it has been shown that it attenuates inflammation and brain damage if given 1 or 6 h (versus 15 min in this study) before ceftriaxone (21,59). Similarly, daptomycin has been shown to be noninferior to ceftriaxone in experimental pneumococcal meningitis (18) and to reduce inflammation and brain damage in this experimental setting (26,27). Our work adds to these studies by a head-to-head comparison of the two nonlytic antimicrobial compounds in a study with a clinically acceptable interval of 15 min (an interval that is accepted for the adjuvant administration of dexamethasone) between administration of the nonlytic antimicrobials and ceftriaxone.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For rifampin, it has been shown that it attenuates inflammation and brain damage if given 1 or 6 h (versus 15 min in this study) before ceftriaxone (21,59). Similarly, daptomycin has been shown to be noninferior to ceftriaxone in experimental pneumococcal meningitis (18) and to reduce inflammation and brain damage in this experimental setting (26,27). Our work adds to these studies by a head-to-head comparison of the two nonlytic antimicrobial compounds in a study with a clinically acceptable interval of 15 min (an interval that is accepted for the adjuvant administration of dexamethasone) between administration of the nonlytic antimicrobials and ceftriaxone.…”
Section: Discussionmentioning
confidence: 95%
“…The number of bacteria in CSF was determined by plating serial dilutions of 10 l of CSF on blood agar plates. Animals were randomized to receive ceftriaxone (n ϭ 32; Rocephin, Roche Pharma; 100 mg/kg of body weight, subcutaneously [s. The dosages of daptomycin, rifampin, and ceftriaxone used in this study were within the range of those used in previously published work (26,27,55,59). CSF was sampled 6 h (24 h postinfection [hpi]) or 22 h (40 hpi) after treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Daptomycin, a lipopeptide antibiotic, has been shown to effectively clear S. pneumoniae in experimental rat, mouse, and rabbit meningitis models (100,177). Treatment with daptomycin led to lower levels of inflammatory cytokines and possibly to less cortical brain damage and neuronal apoptosis than those for treatment with ceftriaxone alone (176,177). Although adjunctive treatment with dexamethasone did not result in a reduction of overall pneumococcal clearance from the CSF, daptomycin penetration into the inflamed meninges was reduced in the presence of adjunctive corticosteroid therapy (136).…”
Section: Nonbacteriolytic Antibioticsmentioning
confidence: 99%
“…In this study, we provide evidence for the competence of grafted hippocampal cells to migrate to the injured hippocampus of infant rats after pneumococcal meningitis. To model the diseases in children with meningitis, we have developed animal models that produce a severe, highly reproducible form of BM in infant rats and mice [14,[41][42][43]. Compared to other experimental models using adult animals, the infant rat model used herein allows investigating pathogenetic mechanisms and their consequences during the development and maturation of the CNS.…”
Section: Discussionmentioning
confidence: 99%